PENINGKATAN MARKETING CAPABILITY UMKM KACANG SANGRAI DI KAMPUNG EKOWISATA KERANGGAN TANGERANG SELATAN - Annuridya Rosyita Pratiwi Octasylva; Shinta Leonita; Gharizi Matiini (Jurnal Abdi Insani, 2023)
Sangrai (Roasted) peanut is a typical product of the city of South Tangerang. There are hundreds of Sangrai peanut craftsmen producing tons of the peanuts each months. However, this product is not yet considered as an iconic food product of South Tangerang due to the lack of promotion and marketing by either the craftsmen or the sellers. The lack of trainings, workshops, and mentoring are several reasons why sangrai peanut craftsmen are still underdeveloped in the case of selling the product.Therefore, the program named improving marketing capability was carried out to improve the ability to market products digitally, using social media and e-commerce, and to make Sangrai peanuts better known to Indonesians as South Tangerang iconic product. The ultimate goal of this activity is to make Sangrai peanurs better known by Indonesians as the food icon of South Tangerang. Improving the marketing capability, especially in Keranggan ecotourism village was carried out in two steps, assisting and training. Assisting activity had been conducted three times, they are assistance in creating sales accounts in e-commerce, making logos, and creating promotional content for social media. On the other hand, the training activity was held in one day with the topic strategies and marketing techniques for Sangrai peanuts. From the implementation of the activities, several outputs were produced, including a new brand logo for package was produced, an e-commerce account which is ready to be used, and the handover supporting instruments for promotion and marketing the product. The logo has been registered to Intellectual Property Rights to avoid plagiarism. E-commerce account are created in Shopee and Tokopedia. The supporting tools are handed over including packaging presser, large cardboard boxes, and 200gram plastic packages. From these activities, we can conclude that the results of research regarding the production of Sangrai peanuts can be forwarder into a community service activity. The activity eventually can support the goal of Keranggan Ecotourism village to have Sangrai peanuts as its iconic foods.